Quality of life assessment in family members of patients with chronic wounds - Erfurt-Berge, Cornelia; Ronicke, Moritz; Richter-Schmidinger, Tanja; Walther, Felix; Renner, Regina (European Journal of Dermatology, 2019)
Familial caregivers are often directly involved in treatment of patients with chronic wounds, however, less is known about their personal impairment, and specific support is lacking for these important members of the therapeutic team regarding wound care. The aim of this study was to investigate the influence of wound care provided by family members on their quality of life, and to create a suitable questionnaire to describe the affected personal aspects. A five-part questionnaire, named ELWA, was created by the authors and answered by 30 familial caregivers of 30 respective patients with chronic leg ulcers. One third of the caregivers reported receiving no medical advice about detailed wound care at all. A lack of information regarding details of the disease correlated with personal strain. Additional costs, anxiety, frustration, and reduced spare-time activities were among the top-rated factors affecting quality of life of family members. The results from this newly created questionnaire point out the needs of familial caregivers of patients with chronic wounds and may help to establish individual support. Implementation of clinical treatment strategies is planned through multicentre application.
CRIS-Team Scopus Importer:2019-12-13
Keywords: chronic wounds; family member; leg ulcer; quality of life; wound care